2017
DOI: 10.1111/pcmr.12559
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of CXCL9, CXCL10, and IFNγ in vitiligo and alopecia areata patients

Abstract: Subscribe to PCMR and stay up-to-date with the only journal committed to publishing basic research in melanoma and pigment cell biology As a member of the IFPCS or the SMR you automatically get online access to PCMR. Sign up as a member today at www.ifpcs.org or at www.societymelanomaresarch.orgIf you wish to order reprints of this article, please see the guidelines here Submit your next paper to PCMR online at http://mc.manuscriptcentral.com/pcmr

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…including Hashimoto thyroiditis, Graves disease 29 and alopecia areata. 11 Interestingly, interface dermatitis is the single most common histopathological presentation in the skin pathology of DRESS, 30 and these IP-10-associated autoimmune diseases can be observed in some individuals with DRESS after their recovery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…including Hashimoto thyroiditis, Graves disease 29 and alopecia areata. 11 Interestingly, interface dermatitis is the single most common histopathological presentation in the skin pathology of DRESS, 30 and these IP-10-associated autoimmune diseases can be observed in some individuals with DRESS after their recovery.…”
Section: Discussionmentioning
confidence: 99%
“…IP‐10 can be secreted by different types of cells under proinflammatory conditions, including monocytes, activated neutrophils, eosinophils, endothelial cells, keratinocytes26 and thyrocytes27 upon stimulation by interferon‐γ. Previous reports have shown that IP‐10 is associated with interface dermatitis or lichenoid tissue reaction28 and autoimmune diseases including Hashimoto thyroiditis, Graves disease29 and alopecia areata 11. Interestingly, interface dermatitis is the single most common histopathological presentation in the skin pathology of DRESS,30 and these IP‐10‐associated autoimmune diseases can be observed in some individuals with DRESS after their recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical signs such as Koebner phenomenon, blurred border, and confetti-like depigmentation have been described as clinical markers of active vitiligo, but these signs only present in a subset of vitiligo patients and are not sufficiently objective 10,11 . Skin tissue biomarkers have been reported, such as basal cell vacuolisation 12 , CD8 + lymphocyte infiltration 13 , and increased expression of heat shock protein-70 14 , CXCL9 15 , and sCD25 16 . However, skin biopsy is a traumatic examination and it is difficult to apply to patients with more than one active period.…”
mentioning
confidence: 99%